Microencapsulation of Baker's Yeast in Gellan Gum Beads Used in Repeated Cycles of Glucose Fermentation. (11th July 2017) - Iurciuc (Tincu), Camelia Elena; Peptu, Catalina; Savin, Alexandru; Atanase, Leonard-Ionuț; Souidi, Kaies; Mackenzie, Grahame; Martin, Patrick; Riess, Gerard; Popa, Marcel
Abstract : The purpose of this work is to prepare ionically cross-linked (with CaCl2 ) gellan particles with immobilized yeast cells for their use in repeated fermentation cycles of glucose. The study investigates the influence of ionic cross-linker concentration on the stability and physical properties of the particles obtained before extrusion and during time in the coagulation bath (the cross-linker solution with different CaCl2 concentrations). It was found that by increasing the amount of the cross-linker the degree of cross-linking in the spherical gellan matrix increases, having a direct influence on the particle morphology and swelling degree in water. These characteristics were found to be very important for diffusion of substrate, that is, the glucose, into the yeast immobilized cells and for the biocatalytic activity of the yeast immobilized cells in gellan particles. These results highlight the potential of these bioreactors to be used in repeated fermentation cycles (minimum 10) without reducing their biocatalytic activity and maintaining their productivity at similar parameters to those obtained in the free yeast fermentation. Encapsulation of Saccharomyces cerevisiae into the gellan gum beads plays a role in the effective application of immobilized yeast for the fermentation process.